The antagonistic MYB paralogs RH1 and RH2 govern anthocyanin leaf markings in Medicago truncatula. Issue 6 (23rd December 2020) - Wang, Chongnan; Ji, Wenkai; Liu, Yucheng; Zhou, Peng; Meng, Yingying; Zhang, Pengcheng; Wen, Jiangqi; Mysore, Kirankumar S.; Zhai, Jixian; Young, Nevin D.; Tian, Zhixi; Niu, Lifang; et al.
Summary: Patterned leaf coloration in plants generates remarkable diversity in nature, but the underlying mechanisms remain largely unclear. Here, using Medicago truncatula leaf marking as a model, we show that the classic M. truncatula leaf anthocyanin spot trait depends on two R2R3 MYB paralogous regulators, RED HEART1 (RH1) and RH2. RH1 mainly functions as an anthocyanin biosynthesis activator that specifically determines leaf marking formation depending on its C‐terminal activation motif. RH1 physically interacts with the M. truncatula bHLH protein MtTT8 and the WDR family member MtWD40‐1, and this interaction facilitates RH1 function in leaf anthocyanin marking formation. RH2 has lost transcriptional activation activity, due to a divergent C‐terminal domain, but retains the ability to interact with the same partners, MtTT8 and MtWD40‐1, as RH1, thereby acting as a competitor in the regulatory complex and exerting opposite effects. Moreover, our results demonstrate that RH1 can activate its own expression and that RH2‐mediated competition can repress RH1 expression. Our findings reveal the molecular mechanism of the antagonistic gene paralogs RH1 and RH2 in determining anthocyanin leaf markings in M. truncatula, providing a multidimensional paralogous–antagonistic regulatory paradigm for fine‐tuning patterned pigmentation.